Features of Densitometric Assessment of Bone Tissue in Young Patients with Hodgkin's Lymphoma - K. M. Badykova; Ju. S. Kitaeva; E. A. Praskurnichij (SINAPS LLC, 2024)
Hodgkin's lymphoma occurs mainly in people aged 15 to 45 years. The use of cytostatic drugs as pathogenetic therapy can cause complications from the musculoskeletal system, such as osteopenia and osteoporosis. To date, the issue of the use of densitometric examination in young patients remains relevant.   The aim of the work. To study the features of densitometric assessment of bone tissue in young patients with Hodgkin's lymphoma.   Materials and methods. The study included 63 patients with an established diagnosis of Hodgkin's lymphoma after pathogenetic therapy and 30 people who make up the control group. All patients underwent a study of bone mineral density by means of two-energy absorptiometry in three areas: the proximal femur, femoral neck and lumbar spine. The Z-criterion was also calculated for each patient. In order to identify the optimal areas of densitometric measurement, the method of one-factor regression analysis was applied.   Results. According to the results of densitometry, a decrease in bone mineral density is more common in the study group compared with the control group. At the same time, in patients with Hodgkin's lymphoma, mineral density decreases equally in the proximal femur and femoral neck. Nevertheless, the manifestations of osteoporosis are more pronounced in the femoral neck, whereas the phenomena of osteopenia prevail in the proximal region. However, a decrease in the Z-criterion in the lumbar spine is observed more often than in the neck and proximal femur.   Conclusion. Early diagnosis opens up the possibility of early prevention of osteoporosis in young patients.